Alzheimer's Disease - Elahi, Montasir (IntechOpen, 2022)
This Edited Volume Alzheimer's Disease is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field. The book comprises single chapters authored by various researchers and edited by an expert in the field, working on Alzheimer's disease and dementia with cutting-edge technology. All chapters are complete in themselves but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors in this research area, and opening new possible research paths for further novel developments.